2014
DOI: 10.1093/mnras/stu2076
|View full text |Cite
|
Sign up to set email alerts
|

The effect of star-spots on the ages of low-mass stars determined from the lithium depletion boundary

Abstract: In a coeval group of low-mass stars, the luminosity of the sharp transition between stars that retain their initial lithium and those at slightly higher masses in which Li has been depleted by nuclear reactions, the lithium depletion boundary (LDB), has been advanced as an almost model-independent means of establishing an age scale for young stars. Here we construct polytropic models of contracting pre-main sequence stars (PMS) that have cool, magnetic starspots blocking a fraction β of their photospheric flux… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 51 publications
2
41
0
Order By: Relevance
“…However, the availability of the necessary photometry and spectral information is far from uniform, leading to uncertainties. Furthermore, the impact of the detailed accretion history, activity, rotation and magnetic field on the location of TTS in the HR diagram may be larger than previously thought (Baraffe et al 2012;Somers & Pinsonneault 2014;Jackson & Jeffries 2014;Bouvier et al 2016). While we cannot escape these issues, we decided to adopt the stellar masses adopted in the studies referred above whenever available.…”
Section: On the Use Of Hα As An Accretion Discriminatormentioning
confidence: 85%
“…However, the availability of the necessary photometry and spectral information is far from uniform, leading to uncertainties. Furthermore, the impact of the detailed accretion history, activity, rotation and magnetic field on the location of TTS in the HR diagram may be larger than previously thought (Baraffe et al 2012;Somers & Pinsonneault 2014;Jackson & Jeffries 2014;Bouvier et al 2016). While we cannot escape these issues, we decided to adopt the stellar masses adopted in the studies referred above whenever available.…”
Section: On the Use Of Hα As An Accretion Discriminatormentioning
confidence: 85%
“…Starspots have a similar affect on lithium burning timescales (Jackson & Jeffries 2014a;Somers & Pinsonneault 2015), which is perhaps not surprising given the deep connection between starspots and magnetic inhibition of convection (Biermann 1941;Deinzer 1965). Nevertheless, if magnetic fields are directly influencing the structure of young stars, they should leave an imprint on the observed lithium abundance distribution in young stellar populations.…”
Section: Lithium Depletionmentioning
confidence: 93%
“…Yet precise measurements of K-and M-dwarfs in eclipsing binary systems have shown that, for a given mass, the radii of stars with 0.2 < M/M < 0.8 are 10-15 per cent larger than predicted by current evolutionary models. Hence, for a given luminosity, the effective transiting exoplanets that are discovered around them and alter the age-dependence of lithium depletion in their photospheres (Jackson & Jeffries 2014a;Somers & Pinsonneault 2014.…”
Section: The Radii Of Low-mass Starsmentioning
confidence: 99%